2010
DOI: 10.1097/nna.0b013e3181f2eb29
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Patient Satisfaction With Nurses' Call Light Responsiveness in 4 US Hospitals

Abstract: Nursing administrators should emphasize increasing staff's call light responsiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 4 publications
0
19
0
1
Order By: Relevance
“…repositioning, hygiene, nourishment, checking equipment is working) (Shepard 2013) and relevant care requirements can be reported to the RN (Gardner et al 2009). Hourly rounding has been linked to decreased use of the call bell for reasons such as pain management, reporting equipment alarms and bathroom assistance (Tzeng 2010, Tzeng & Yin 2010. Regular check-ups on patients can reduce adverse events (Mitchell et al 2014).…”
Section: What Are the Key Findings?mentioning
confidence: 99%
See 1 more Smart Citation
“…repositioning, hygiene, nourishment, checking equipment is working) (Shepard 2013) and relevant care requirements can be reported to the RN (Gardner et al 2009). Hourly rounding has been linked to decreased use of the call bell for reasons such as pain management, reporting equipment alarms and bathroom assistance (Tzeng 2010, Tzeng & Yin 2010. Regular check-ups on patients can reduce adverse events (Mitchell et al 2014).…”
Section: What Are the Key Findings?mentioning
confidence: 99%
“…). Hourly rounding has been linked to decreased use of the call bell for reasons such as pain management, reporting equipment alarms and bathroom assistance (Tzeng , Tzeng & Yin ). Regular check‐ups on patients can reduce adverse events (Mitchell et al .…”
Section: Introductionmentioning
confidence: 99%
“…Surveys conducted with nurses and patients indicate that pain management, personal assistance, bathroom assistance and equipment alarms (i.e., intravenous pumps) were among the top 5 reasons for pushing the call bell (6, 7). Structured hourly rounding which addresses these important “Ps” may thus allow nurses to provide more responsive and uninterrupted care.…”
mentioning
confidence: 99%
“…One study examined these interruptions and found that accidentally pushing the call button was the fifth highest ranked reason for call button use. 2 Thanks to this new system, nursing units are experiencing improved workflow as a result of the division of call assignments to the appropriate staff member-either the nurse or UAP. Each staff member receives fewer notifications under the centralized system, meaning that nurses have more time to spend on other vital responsibilities.…”
Section: Patient Complaints About Call Button and Nurse Responsivenessmentioning
confidence: 99%